Subterranean gametophytic axes in the primitive liverwort Haplomitrium harbour a unique type of endophytic association with aseptate fungi - Carafa, Anna (The New phytologist, 2003)
•  Haplomitrium, a primitive liverwort taxon with only remote affinities to other liverwort groups, develops root-like subterranean axes harbouring fungal endophytes. Here we report on the fungal association in H. gibbsiae and H. ovalifolium, using light and electron microscopy. •  The epidermal cells of subterranean axes secrete abundant mucilage that harbours aseptate fungal hyphae. The fungus penetrates the epidermal cells and forms intracellular arbuscules invested by the host cytoplasm. Infection is restricted to epidermal cells in H. gibbsiae, whereas in H. ovalifolium the fungus also infects the cortical cells immediately adjacent, where it forms prominent swellings ('lumps'). In H. gibbsiae similar fungal swellings are formed in the epidermal cells along with arbuscules. In both species the lumps undergo cytoplasmic degeneration and collapse, showing a shorter lifespan than the arbuscules. •  The fungal infection in Haplomitrium presents affinities with symbiotic associations with glomeromycotean fungi in higher plants (arbuscular mycorrhizas) and thalloid liverworts. However, the pattern of fungal morphogenesis in Haplomitrium has no precedent in bryophytes nor in higher plants. •  Considering the Glomeromycota as the most ancient lineage of mycorrhizal fungi, and Haplomitrium as basal in land plant phylogenies, the association described here may be the most primitive land plant-fungal symbiosis documented to date